Challenges and creativities in encouraging students to read in English language lessons: In-depth interview with junior high school teachers - Ikhsanudin, Ikhsanudin; Lestari, Rika (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
This research investigates the challenges faced by English teachers in motivating junior high students to read within the context of implementing an emancipatory curriculum in Indonesia. Utilizing a semi-structured in-depth interview method, the study, conducted in four government schools in Pontianak in 2023, engaged four English teachers as respondents and one as an interviewer. Respondents were chosen based on their active involvement in daily professional activities. Following a predetermined interview protocol, the interviewer conducted one-on-one sessions, exploring teachers’ experiences, opinions, and emotions regarding efforts to promote English reading in their schools. The collected data underwent coding and interpretation, revealing teachers as crucial facilitators creatively addressing challenges, particularly in student motivation. Their adaptability and innovative programs foster diverse reading engagement strategies. Schools implement enhancements such as differentiated learning and literacy programs, extending to character development and teacher professionalism. Those efforts were the teachers’ creativity to elevate English teaching and learning in those four schools, particularly to promote reading activities during the early implementation of emancipatory curriculum. The findings emphasize the necessity for ongoing professional development, collaboration to address resource challenges, and the promotion of effective communication and collaboration among educators to enhance student engagement through innovative teaching.